Measuring the influence of green HRM, lean HRM, and agile HRM on sustainable manufacturing - Ishaq Ibrahim; Rany Abu Eitah (Heritage and Sustainable Development)
This research targets Malaysian manufacturing sustainability as one of the most important industries that affect the country’s income. This study aims to examine the relationships between green human resource management (GHRM), lean human resource management (LHRM), and agile human resource management (AHRM) in terms of sustainable manufacturing in Malaysia. For the sake of achieving the objectives of this particular research quantitative method was employed on 562 respondents from the Malaysian manufacturing industry. The data was analyzed via SPSS in the initial and descriptive analysis, while SEM-AMOS was used in hypothesis testing. The findings of the research supported the hypothesis of the significant impact of GHRM on sustainable manufacturing in Malaysia, the significant impact of LHRM on sustainable manufacturing in Malaysia, and the significant impact of AHRM on sustainable manufacturing in Malaysia. GHRM is the crucial base variable to implement other variables (LHRM & AHRM) in the Malaysian manufacturing industry, whereas GHRM has the highest impact and is mostly implemented among the employees and factories.